2020
DOI: 10.1055/s-0040-1710543
|View full text |Cite
|
Sign up to set email alerts
|

Resident Operative Vaginal Delivery Volume after Educational Curriculum Implementation

Abstract: Objective The percentage of operative vaginal deliveries (OVDs) in the United States has sharply declined. In May 2016, our institution's obstetrics and gynecology (OB/GYN) residency program implemented a twice-yearly OVD curriculum consisting of didactics and simulation. We sought to evaluate the impact of this curriculum. Study Design We performed a retrospective cohort study of all deliveries at our institution from July 2011 to May 2018. Deliveries were evaluated quarterly for the pre- (July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Additionally implementation of formal OVD curricula have proven successful in increasing OVD rates within residency programs, and could be considered for widespread adoption. 17 In an analysis of outcomes of OVD performed by residents under the supervision of an attending obstetrician compared to outcomes when performed by the attending obstetrician alone, there was no difference in rates of neonatal or maternal morbidity. 18 Simulation models have developed to increase operator technique, comfort, knowledge, and patient outcomes.…”
Section: Resultsmentioning
confidence: 96%
“…Additionally implementation of formal OVD curricula have proven successful in increasing OVD rates within residency programs, and could be considered for widespread adoption. 17 In an analysis of outcomes of OVD performed by residents under the supervision of an attending obstetrician compared to outcomes when performed by the attending obstetrician alone, there was no difference in rates of neonatal or maternal morbidity. 18 Simulation models have developed to increase operator technique, comfort, knowledge, and patient outcomes.…”
Section: Resultsmentioning
confidence: 96%
“…In most of the studies that provided this information, significant increases in the rates of AVB were not associated with significant increases in adverse maternal or perinatal outcomes ( online supplemental file 8 ). Out of the five studies 27 38 39 43 44 conducted in HIC countries with statistically significant increases in the use of forceps, one 39 did not assess any maternal or perinatal outcomes, and one 38 reported non-significant changes in adverse maternal and perinatal outcomes (3rd/4th degree tears, low 5 min Apgar scores). The other three HIC studies 27 43 44 reported that increased rates of forceps were associated with either non-significant changes in several adverse maternal or perinatal outcomes (3rd/4th degree tears, birth injuries, overall neonatal complications, composite neonatal morbidity, low Apgar scores) or significant decreases in some of these outcomes (4th degree tears, overall maternal complications, postpartum haemorrhage, low cord pH) in this population.…”
Section: Resultsmentioning
confidence: 99%
“…The two studies that assessed participants’ changes in knowledge and skills (Kirkpatrick level-2) reported significant increases in these outcomes immediately after the training intervention. 39 47 Only one study assessed participants’ satisfaction with the intervention (Kirkpatrick level-1) and reported that the trainees (mostly midwives) reacted positively to all lectures and breakout sessions (mean scores 9.3/10). 47 None of the studies assessed maternal birth experience or satisfaction during the interventions.…”
Section: Resultsmentioning
confidence: 99%
“…25 A study conducted at our institution emphasized the importance of training residents on the utilization of forceps as an alternative to a cesarean delivery in the second stage of labor. 25 Fetal malpresentation is another indication that increases the cesarean rates. Breech presentation complicates around 4% of term deliveries; however, only one-third are offered an ECV, and if counseling does occur, some patients still refuse an ECV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to strictly conforming to the contemporary labor definitions, an increase in the utilization of operative vaginal delivery procedures is likely to decrease cesarean deliveries caused by second stage arrest. 3.3% of operative vaginal deliveries with 1.5% being forceps were performed at our hospital in 2016 compared to a national average of 3.1% operative deliveries and 0.5% forceps (25). A study conducted at our institution emphasized the importance of training residents on the utilization of forceps as an alternative to a cesarean delivery in the second stage of labor (25).…”
Section: Accepted Manuscriptmentioning
confidence: 91%